2020
DOI: 10.1186/s12903-020-01238-9
|View full text |Cite
|
Sign up to set email alerts
|

Education and income-based inequality in tooth loss among Brazilian adults: does the place you live make a difference?

Abstract: Background Socioeconomic inequalities in tooth loss might be minimized or potentialized by the characteristics of the context where people live. We examined whether there is contextual variation in socioeconomic inequalities in tooth loss across Brazilian municipalities. Methods Data from the 2010 National Oral Health Survey of 9633 adults living in 157 Brazilian municipalities were used. The individual socioeconomic indicators were education and household income. At th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 56 publications
(72 reference statements)
8
21
1
3
Order By: Relevance
“…Importantly in the current study, more missing teeth were related to low level of education and weak oral hygiene practices. These results were in line with previous findings, as there was a social gradient in tooth loss by education and their results showed that living in disadvantaged municipalities cannot overcome the risk associated with low schooling [38]. Moreover, it has been reported that experience of dental caries was associated with refugee behaviors, including poor dental hygiene methods and level of education, where higher education levels provided a better understanding of oral and general health [2] Previous studies assessing awareness of dental implants have shown high levels (77.0% and 70.1% in American and a Norwegian samples, respectively [39,40]), similar to the present study (83.4%); however, this is subjective awareness, and when the actual knowledge was tested (objective awareness), only 1.9% were extremely knowledgeable and 10.4% had moderate knowledge about dental implants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly in the current study, more missing teeth were related to low level of education and weak oral hygiene practices. These results were in line with previous findings, as there was a social gradient in tooth loss by education and their results showed that living in disadvantaged municipalities cannot overcome the risk associated with low schooling [38]. Moreover, it has been reported that experience of dental caries was associated with refugee behaviors, including poor dental hygiene methods and level of education, where higher education levels provided a better understanding of oral and general health [2] Previous studies assessing awareness of dental implants have shown high levels (77.0% and 70.1% in American and a Norwegian samples, respectively [39,40]), similar to the present study (83.4%); however, this is subjective awareness, and when the actual knowledge was tested (objective awareness), only 1.9% were extremely knowledgeable and 10.4% had moderate knowledge about dental implants.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly in the current study, more missing teeth were related to low level of education and weak oral hygiene practices. These results were in line with previous findings, as there was a social gradient in tooth loss by education and their results showed that living in disadvantaged municipalities cannot overcome the risk associated with low schooling [ 38 ]. Moreover, it has been reported that experience of dental caries was associated with refugee behaviors, including poor dental hygiene methods and level of education, where higher education levels provided a better understanding of oral and general health [ 2 ]…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of previous studies to have identified age and socioeconomic conditions as risk factors for tooth loss [11,12,28]. Aging populations have accumulated oral and non-communicable health conditions, and so remain susceptible to ongoing tooth loss.…”
Section: Plos Onesupporting
confidence: 92%
“…While previous research has identified the determinants of tooth loss, most of this literature examined only edentulism and did not examine incremental tooth loss, which is a far more prevalent oral state [11]. Moreover, those studies were mostly based on cross-sectional data or examined a few variables using classical statistical modeling rather than predictive modeling [11,12,24]. We found that machine-learning models performed better than conventional statistical methods (logistic regression) for predicting edentulism and the absence of a functional dentition.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation